An evaluation of menstrual health apps’ functionality, inclusiveness, and health education information - Emma Bucher; Callie Sharkey; Abby Henderson; Briette Basaran; Sarah Meyer; Chen X. Chen (BMC Women's Health)
Abstract Background Menstrual health apps have become increasingly popular, providing users with a tool to monitor and learn about menstrual cycles, symptoms, and management. While previous research examined different aspects of menstrual health apps (e.g., fertility tracking), few examined menstrual health apps comprehensively to examine the menstrual health apps’ functionality, inclusiveness, and health education information. The purpose of this study was to evaluate menstrual health apps’ functionality, inclusiveness, and health education information. Methods In this descriptive study, two reviewers independently searched, screened, and evaluated each app using a standardized tool. Three terms (i.e., “period pain,” “period app,” and “menstrual cramp”) were used to search the Apple App Store. Apps were also cross-searched on the Google Play Store. We screened 60 apps. After excluding duplicates and apps that did not meet the inclusion criteria, 14 apps were evaluated on their functionality (user experience, internet and language accessibility, privacy, cycle-prediction, and symptom-tracking ability), inclusiveness (cycle lengths and regularities, fertility goals, and gender expressions and sexualities), and menstrual health education information (credibility and comprehensiveness, presence of additional health information, and information on when to seek care). We used a modified version of the Mobile App Rating Scale to score each app. Results For functionality, half of the apps had third-party advertisements. Most (71.4%) did not require cellular connection to utilize menstrual symptom-tracking, and 71.4% shared user data with third parties. All had cycle-prediction and symptom-tracking functions. The mean number of relevant symptoms tracked was 17.5 (SD = 5.44). None of the apps used or cited validated symptom measurement tools. For inclusiveness, all apps could be tailored to cycle lengths other than 28 days, 85.7% had ovulation prediction functions, 50% had neutral or no pronouns, and 92.9% allowed users to input at least one contraceptive type. For health education information, 42.9% cited medical literature. Conclusion This study suggests a lack of professional involvement and gender inclusivity in menstrual health app development. Healthcare professionals should educate themselves on apps’ functionality, inclusiveness, and health education information before recommending apps. Additional research is needed to understand diverse users’ perspectives on menstrual health apps.